Legalisasi Perkawinan Tidak Tercatat: Kebijakan Nikah Siri dan Normalisasi Isbat Nikah di Aceh - Sulaiman, Mulyadi (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2025)
This policy paper analyzes the phenomenon of the normalization of isbat nikah (marriage legalization through court confirmation) in Aceh, which has shifted from its intended role as an ultimum remedium to a dominant legalization procedure for unregistered marriages. This trend has created a significant gap in legal certainty for families and the accuracy of population data, further exacerbated by the prevalence of nikah siri (unregistered marriages), and poses a high level of urgency due to its impact on the rights of women and children. Employing a qualitative approach, this paper examines relevant regulations, literature studies, and evaluates policy alternatives using William N. Dunn's scoring method. The analysis reveals that Aceh Governor Regulation No. 25 of 2017 institutionalized isbat nikah as the primary route for marriage legalization, thereby contributing to its normalization and worsening the low rate of marriage registration. The root causes include misalignment between national and regional legal norms, the absence of comprehensive preventive programs against nikah siri, and weak coordination and integrity in population administrative data. The normalization of isbat nikah significantly undermines both the protection of citizens' rights and the reliability of demographic data. Accordingly, this paper recommends the implementation of a comprehensive national policy to tighten the interpretation and procedures of isbat nikah. The recommendation emphasizes reaffirming isbat nikah as an ultima ratio mechanism, with stricter evidentiary requirements, and addressing Aceh's unique context to ensure legal certainty and the protection of citizens’ fundamental rights